2005
DOI: 10.1007/s00335-005-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of jejunal Peyer’s patches in juvenile and adult pigs

Abstract: Peyer's patches are organized lymphoid tissues of the small intestine that play a critical role in disease resistance and oral tolerance. Peyer's patches in the jejunum contain lymphocytes, dendritic cells, macrophages, villous epithelium, and specialized follicle-associated epithelium. Little is known about the mechanisms and processes by which cells of the Peyer's patches discriminate food nutrients and commensal microflora from pathogenic microbiota. We hypothesize that the jejunal Peyer's patches express g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 79 publications
0
18
0
1
Order By: Relevance
“…These results might reflect the massive regulation of the reorganization of mucosal immune response to food antigens following weaning (which occurred at 28 days of age), aside of constant replacement of enterocytes by regeneration of epithelial cells from crypts and the constant production of protective mucus coat in young pigs [29]. In a similar way, Machado et al [30] reported significantly higher expression of genes associated with growth and apoptosis in the jejunal Peyer's patches in 7-weeks old pigs compared to 6-months old ones. A close examination of these canonical pathways revealed notable difference in expression patterns of individual transcription factors involved in intestine development and cellular function amongst the various segments of the porcine intestine.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These results might reflect the massive regulation of the reorganization of mucosal immune response to food antigens following weaning (which occurred at 28 days of age), aside of constant replacement of enterocytes by regeneration of epithelial cells from crypts and the constant production of protective mucus coat in young pigs [29]. In a similar way, Machado et al [30] reported significantly higher expression of genes associated with growth and apoptosis in the jejunal Peyer's patches in 7-weeks old pigs compared to 6-months old ones. A close examination of these canonical pathways revealed notable difference in expression patterns of individual transcription factors involved in intestine development and cellular function amongst the various segments of the porcine intestine.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to the physical barrier, the intestinal tissues are also able to provide effective innate defence against luminal threats discriminating between pathogenic microorganisms and harmless substances [30]. During the complete life time, there is a permanent crosstalk among epithelial cells, bacteria and the gut-associated lymphoid tissue (GALT), which are mainly composed of Peyer's patches, mesenteric lymph nodes, and lymphocytes distributed throughout the lamina propria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, pouco se sabe sobre seus mecanismos de ação, notadamente no que se refere aos processos envolvidos na identificação dos patógenos. Para melhor entender as funções dessas estruturas, Machado et al (2005) investigaram os padrões normais de expressão gênica nas placas de Peyer presentes no jejuno de suínos jovens e adultos, criados sob condições convencionais. Utilizando microarrays de cDNA com 2.604 seqüências gênicas, estes autores verificaram que tanto nos animais jovens, quanto nos adultos, as placas de Peyer apresentavam diversos genes relacionados com a imunidade inata estimulados, enquanto que um grupo de genes relacionados com o crescimento celular e com a apoptose tiveram a alterações histológicas em peixes, produzindo inclusive o hermafroditismo e induzindo a produção de vitelogenina (característica de fêmeas sexualmente maduras) em indivíduos machos.…”
Section: And the Number Of Null Hypotheses Rejected (R) Or Not (M -R)unclassified
“…This microarray is comprised of 70-mer oligonucleotide (Qiagen-NRSP8 array) and has been recently validated and shown to be informative and specific and thus an appropriate tool for porcine functional genomics studies and for modeling the pig in physiological questions. Recently Machado et al (2005) have used this functional genomics approach to monitor changes in gene expression in jejunal Peyer's patches in both juvenile and adult pigs.…”
Section: Genomic Approaches To Pig Digestive Physiologymentioning
confidence: 99%